2002
DOI: 10.1002/hbm.10056
|View full text |Cite
|
Sign up to set email alerts
|

Eyeblink‐related areas in human cerebellum as shown by fMRI

Abstract: Classical eyeblink conditioning is used frequently to study the role of the cerebellum in associative learning. To understand the mechanisms involved in learning, the neural circuits that generate the eyeblink response should be identified. The goal of the present study was to examine cerebellar regions that are likely to control the human eyeblink response using event-related functional magnetic resonance imaging (fMRI). In 14 healthy volunteers eyeblinks were evoked by unilateral air-puff stimulation (total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 79 publications
6
47
0
Order By: Relevance
“…Other studies have implicated the posterior cerebellar cortex in CR acquisition, but with a limited role in the timing of the CR (e.g., Attwell, Rahman, and Yeo, 2001). These findings in rabbits have been supported in humans using positron emission tomography (Logan and Grafton, 1995;Blaxton et al, 1996) and functional MRI (Ramnani et al, 2000;Dimitrova et al, 2002). Clinically, insults to the cerebellum have been shown to markedly impair acquisition of the conditioned eyeblink response (Daum et al, 1993;Woodruff-Pak et al, 1996).…”
Section: Introductionmentioning
confidence: 89%
“…Other studies have implicated the posterior cerebellar cortex in CR acquisition, but with a limited role in the timing of the CR (e.g., Attwell, Rahman, and Yeo, 2001). These findings in rabbits have been supported in humans using positron emission tomography (Logan and Grafton, 1995;Blaxton et al, 1996) and functional MRI (Ramnani et al, 2000;Dimitrova et al, 2002). Clinically, insults to the cerebellum have been shown to markedly impair acquisition of the conditioned eyeblink response (Daum et al, 1993;Woodruff-Pak et al, 1996).…”
Section: Introductionmentioning
confidence: 89%
“…Several previous studies have reported that the cerebellar vermis and cerebellar hemisphere were activated during horizontal eye movement (Stephan et al 2002;Hüfner et al 2008) and blinking (Van Eimeren et al 2001;Dimitrova et al 2002). According to these reports, the area that was activated by horizontal eye movement almost overlapped with the area activated by lid movement.…”
Section: Cerebellummentioning
confidence: 91%
“…According to the learning theories of Albus and Marr [34,35] , it seemed reasonable that plasticity could be generated in the unilateral cerebellum contralateral to the stimulated side of the US during the unilateral EBCC. Up to now, there some data have indirectly suggested the existence of this contralateral plasticity [10][11][12][13][14][15] . Moreover, there are anatomical pathways through which the unilateral cerebellum could control bilateral eyeblink responses.…”
Section: Role Of the Contralateral Cerebellum In The Acquisition Of Umentioning
confidence: 93%
“…To test whether any learning had occurred during these inactivation sessions, training was continued for six more sessions without inactivation. On session 5, the second session without inactivation, the CR incidence, CR peak amplitude and CR onset latency of the L-MSC guinea pigs were indistinguishable from those of the control animals on session 2 [Incidence: t (15) These results indicated that (1) significant acquisition of the left CRs occurred during these training sessions in either group and (2) during the 'equivalent normal session 2 to 7', the L-MSC animals exhibited the same incidence, peak amplitude, and onset latency of left CR as those of the control animals during sessions 2 to 7. On session 11, microinjections of muscimol into the left (Figures 3 and 4).…”
Section: Left Cr Acquisition In the L-msc Groupmentioning
confidence: 99%
See 1 more Smart Citation